Representing the "Historical Centre" of Bologna: Preservation Policies and Reinvention of an Urban Identity - De Pieri, Filippo; Scrivano, Paolo (Urban History Review / Revue d'histoire urbaine, 2004)
This article analyzes the visual and textual representations of the "historical centre" of Bologna before and after 1969 the year when the first of the city's celebrated plans for the preservation of the ancient urban fabric were approved. In spite of the attempts made by architects and planners to precisely and "technically" define the object of the plans, the notion of "historical city centre" remained a vague and ambiguous one. Conflicting images of history, tradition, and centrality shaped the preservation policies, and were in turn reshaped by them. The visual, historical, and political discourse behind the Bologna plans intentionally brought together a multiplicity of local and non-local cultures, resulting in an overall reinvention of both a local identity and an idea of the city of the past.